Clinical peculiarities of measles in children from the Ternopil region, Ukraine - Pavlyshyn, Halyna; Horishna, Ivanna (Pediatria Polska - Polish Journal of Paediatrics, 2019)
The medical cards of children hospitalised in the Infectious Department of Ternopil Children’s Hospital were analysed. Children, mainly unvaccinated or incompletely vaccinated, form the majority in the structure of measles morbidity in the Ternopil region of Ukraine. The disease has typical cyclic course with pathognomonic symptoms and is mainly moderate and uncomplicated. Complications are predominantly characterised by respiratory and digestive system involvement. Prolongation of the prodromal period with prodromal rash and shortening or prolongation of the exanthema period in some patients, characterised by specific rash staging, are the main clinical peculiarities in children of this region. Leukopaenia, thrombocytopaenia, eosinophilia, and leukocytic left shift are typical for the prodromal and exanthema period, and normocytosis or leukocytosis with lymphocytosis are typical for the pigmentation period. A biochemical blood test shows the impairment of the liver function in some cases. Chest X-ray shows strengthening of the pulmonary pattern in the base of the lungs in the case of complications with bronchitis and infiltrates in the lower lobes in case of pneumonia.